2019
DOI: 10.21037/jtd.2018.12.09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of improving outcomes after esophagectomy on the short- and long-term: a review of literature

Abstract: An esophagectomy is still correlated with a high morbidity rate, despite advances made in minimally invasive surgery, enhanced recovery after surgery (ERAS) and centralization of this type of surgery. The short-term benefits are clearly described for esophageal cancer surgery patients, however, the longterm effects are yet to be determined. In colorectal cancer, the association between complications, especially anastomotic leakage, shows detrimental effects on long-term survival and cancer recurrence. In esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 52 publications
(82 reference statements)
0
15
1
Order By: Relevance
“…It also has been shown that standardized protocols like ERAS protocols for surgical cancer patients lead to shorter in-hospital stays, decreased complications and longer overall survival [ 31 , 32 , 33 , 51 ]. Therefore, our clinic uses standardized pathways for esophageal cancer patients to improve postoperative outcomes of esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has been shown that standardized protocols like ERAS protocols for surgical cancer patients lead to shorter in-hospital stays, decreased complications and longer overall survival [ 31 , 32 , 33 , 51 ]. Therefore, our clinic uses standardized pathways for esophageal cancer patients to improve postoperative outcomes of esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these findings the oncological patients at the Surgical Department of the University Hospital Mannheim are encouraged to take part in nutritional consulting at our clinic or at other specialized practices before and after surgery. Our clinic uses standardized protocols, guided by “Enhanced recovery after surgery“(ERAS) protocols, to improve postoperative outcome and length of hospital stay [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…17,18 During the study period, multiple modifications were made to the perioperative care path to improve outcomes after esophagectomy, such as centralization of care and introduction of enhanced recovery after surgery programs. 19 The effect of these modifications is reflected by an increase in "no severe postoperative complications" (Figure 2). Subsequently, reduction of complications after esophagectomy could also improve long-term survival.…”
Section: Commentmentioning
confidence: 99%
“…Although surgery is an effective treatment for EC, most patients tend to be at an advanced stage at the time of diagnosis [5,6]. Thus, radiotherapy (RT) plays a well-defined role in the management of patients with inoperable locally advanced EC [7].…”
Section: Introductionmentioning
confidence: 99%